Magnetic core with high magnetic conductivity as well as preparation method and application of magnetic core

Through two heat treatments and magnetic field heat treatment, the problem of incomplete and uneven grain precipitation of amorphous magnetic core at high temperatures is solved, and the magnetic permeability in the entire frequency band is significantly improved, ensuring the high of the magnetic core at different frequencies Performance performance.

CN119252640APending Publication Date: 2025-01-03FOSHAN CITY ZHONGYAN AMORPHOUS TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411588559.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, amorphous magnetic cores often experience incomplete grain precipitation, unevenness and excessive growth during high-temperature heat treatment, resulting in different magnetic permeability performance in different frequency bands, and the highest magnetic permeability state cannot be maintained, which limits the Improved core performance.

Method used

Using two heat treatments and magnetic field heat treatment methods, the amorphous magnetic core is heated evenly through the first heat treatment, and then the temperature and pressure are increased in the second heat treatment, combined with a slow temperature increase rate and appropriate insulation time to ensure the grains. The nanograins are uniformly precipitated at high temperatures, and the nanograins are completely turned by magnetic field heat treatment to avoid uneven heat and excessive growth of grains.

Benefits of technology

The magnetic core significantly improves the permeability in the entire frequency band, ensuring the high performance of the magnetic core at different frequencies, and the permeability is increased by more than 100% at 1kHz, 10kHz and 100kHz respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252640A_ABST
    Figure CN119252640A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of magnetic materials, and particularly discloses a high-permeability magnetic core and a preparation method and application thereof. According to the method, heat treatment is conducted twice at certain pressure and temperature, then magnetic field heat treatment is conducted, the amorphous magnetic core is induced to achieve nanocrystallization and grain homogenization, the problems of nonuniform nucleation and excessive growth of nanocrystals in conventional heat treatment are effectively solved, the magnetic conductivity of the magnetic core at different frequencies is comprehensively improved, and the magnetic conductivity of the amorphous magnetic core is improved. The purpose of improving the magnetic conductivity of the full-band magnetic core to the maximum extent is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnetic materials, and in particular relates to a magnetic core with high magnetic permeability and a preparation method and application thereof. Background Art

[0002] Iron-based amorphous / nanocrystalline soft magnetic alloys are usually made of amorphous strips by high-speed copper roller rapid cooling process, and the amorphous strips are wound into amorphous cores. Amorphous cores generally need to undergo appropriate heat treatment processes to finely control the microstructure of the alloy, that is, a single magnetic α-Fe phase is precipitated on the amorphous matrix and transformed into a dual-phase coexistence structure of amorphous and nanocrystalline to form a magnetic core. This special dual-phase nanostructure is also the main reason why the magnetic core exhibits excellent comprehensive soft magnetic properties. Therefore, the heat treatment process of the magnetic core plays a decisive role in obtaining high-performance magnetic cores.

[0003] In conventional heat treatment methods for amorphous magnetic cores, such as annealing in an atmosphere furnace, amorphous magnetic cores often experience incomplete grain precipitation, uneven grain precipitation, and excessive growth under high-temperature heat treatment. All of the above conditions will deteriorate the performance of the obtained magnetic core, especially significantly reduce the magnetic permeability of the magnetic core. Moreover, the magnetic permeability is different at different frequencies, resulting in different degrees of improvement in the magnetic permeability at different frequency bands by the heat treatment process. Therefore, general magnetic cores cannot maintain the highest magnetic permeability at different frequency bands. Therefore, the heat treatment process based on the existing technology has great limitations in improving the magnetic permeability of the magnetic core, and it is urgent to develop a new magnetic core preparation technology to improve the magnetic permeability of the magnetic core to the greatest extent possible. Summary of the invention

[0004] In view of the limitations of the heat treatment process in the prior art on improving the magnetic permeability of the magnetic core, the present invention will provide a magnetic core with high magnetic permeability and a preparation method and application thereof.

[0005] To achieve the above purpose, the following technical solutions are specifically included:

[0006] A method for preparing a magnetic core comprises the following steps:

[0007] (1) subjecting the amorphous magnetic core to a first heat treatment and a second heat treatment in sequence, cooling and reducing the pressure to obtain a pre-burned magnetic core; the temperature of the first heat treatment is 400-480° C., the temperature of the second heat treatment is 490-540° C., the pressure of the first heat treatment is 50-100 MPa, and the pressure of the second heat treatment is 90-160 MPa;

[0008] (2) The pre-burned magnetic core is subjected to magnetic field heat treatment and cooled to obtain the magnetic core.

[0009] In the method of the present invention,

[0010] The present invention firstly performs a first heat treatment to make the amorphous magnetic core evenly heated, thus providing a basis for a second heat treatment; then the temperature is raised to the second heat treatment temperature, and the pressure is continuously increased, through a slow heating rate and selecting a suitable holding time, to ensure that the grains have enough time to precipitate at a relatively high temperature, and grow slowly and evenly under the action of the air pressure, thereby avoiding uneven heating caused by overheating, incomplete grain precipitation caused by too short a time, or excessive grain growth caused by too long a holding time; finally, combined with magnetic field heat treatment, the nano-crystal grains are completely turned, and the force field heat treatment and the magnetic field heat treatment as a whole make the grains in the magnetic core precipitate completely and have uniform size, thereby achieving the purpose of improving the full-band magnetic permeability of the magnetic core.

[0011] Preferably, in step (1), the time of the first heat treatment is 70-180 min, and the heating rate of the first heat treatment is 1-30° C. / min.

[0012] Preferably, the time of the second heat treatment is 70-180 min, the heating rate of the second heat treatment is 1-5° C. / min, and the cooling rate is 5-200° C. / min.

[0013] In the method of the present invention, in step (1), the first heat treatment and the second heat treatment are mainly aimed at crystallizing the amorphous magnetic core, aiming to promote the precipitation of a large number of fine α-Fe nano-grains on the amorphous matrix; in step (2), the grains in the magnetic core are induced to grow in an oriented manner along the direction of the magnetic field through the action of the magnetic field while precipitating and growing, and appropriate magnetic anisotropy is introduced under the action of the external magnetic field; therefore, the precipitation, size and growth orientation of nano-grains are regulated by the method of the present invention, thereby improving the comprehensive soft magnetic properties of the obtained nanocrystalline magnetic core.

[0014] Preferably, in step (1), the pressurization methods of the first heat treatment and the second heat treatment are each selected from at least one of pressurization by inert gas pressure and pressurization by mold extrusion; the amorphous magnetic core in step (1) is formed by winding an amorphous strip, and the magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the amorphous magnetic core.

[0015] Preferably, in step (1), the amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%, V 0-10%.

[0016] Further preferably, the amorphous magnetic core is Fe 73.5 Si 15.5 B7Cu1Nb3、Fe 73.5 Si 15.5B7Cu1V1Nb2、Fe 73.5 Si 13.5 B9Cu1Nb3、Fe 63.5 Ni 10 Si 15.5 B7Cu1Nb3、Fe 63.5 Co5Ni5Si 15.5 B7Cu1Nb3、Fe 68.5 Co5Si 15.5 At least one of B7Cu1Nb3.

[0017] Preferably, in step (1), the cooling and depressurization is carried out by first naturally cooling the system to below 200°C and then releasing the pressure of the system to atmospheric pressure, with a cooling rate of 10-500°C / min.

[0018] Preferably, in step (2), the temperature of the magnetic field heat treatment is 460-530° C., the time of the magnetic field heat treatment is 10-180 min, and the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.

[0019] Preferably, in step (2), the rate of heating to the magnetic field heat treatment temperature is 1-20°C / min.

[0020] Preferably, in step (2), the cooling method is natural cooling.

[0021] Preferably, the magnetic permeability of the magnetic core is greater than or equal to 35,000.

[0022] Further preferably, at a frequency of 1 kHz, the magnetic permeability of the magnetic core is 160,000-250,000, at a frequency of 10 kHz, the magnetic permeability of the magnetic core is 140,000-200,000, and at a frequency of 100 kHz, the magnetic permeability of the magnetic core is 35,000-40,000.

[0023] Further preferably, the magnetic core contains nano-sized α-Fe grains.

[0024] The present invention also provides an application of the magnetic core in the preparation of new energy vehicles, photovoltaic energy storage equipment, electronic camera equipment, and 5G communication equipment. The magnetic core of the present invention has a high magnetic permeability and is more suitable for use in the preparation of the above-mentioned equipment.

[0025] Compared with the prior art, the present invention has the following beneficial effects: in the method of the present invention, two heat treatments are first performed at a certain pressure and temperature, and then a magnetic field heat treatment is performed to induce the amorphous magnetic core to achieve nanocrystallization and grain homogenization, which effectively solves the problems of uneven nucleation and excessive growth of nanocrystals in conventional heat treatment, comprehensively improves the magnetic permeability of the magnetic core at different frequencies, and achieves the purpose of maximizing the magnetic permeability of the magnetic core in the full frequency band. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the X-ray diffraction (XRD) pattern of the homemade amorphous ribbon.

[0027] Figure 2 A comparison diagram of the magnetic domain structures between Example 1 (left) and Comparative Example 5 (right).

[0028] Figure 3 This is a physical picture of the magnetic core prepared in Example 1.

[0029] Figure 4 Graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of Examples 1 to 13.

[0030] Figure 5 This is a graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of comparative examples 1 to 5. DETAILED DESCRIPTION

[0031] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0032] Amorphous ribbons can be made by ourselves or purchased from the market. The amorphous ribbons used below are made by ourselves, among which Fe 73.5 Si 15.5 B7Cu1V1Nb2 XRD as attached Figure 1 As shown; the homemade method may include the following processes: (1) component ratio; (2) master alloy smelting; (3) then through strip throwing and strip winding, to obtain the corresponding amorphous strip.

[0033] Example 1

[0034] (1) The alloy Fe in atomic percentage 73.5 Si 15.5 The B7Cu1V1Nb2 amorphous strip is wound into an amorphous magnetic core, and then the amorphous magnetic core is placed in a gas furnace body, evacuated, filled with inert gas argon gas, so that the system has a certain gas pressure, heated to the first heat treatment temperature of 430°C at a heating rate of 15°C / min, and at the same time, argon gas is continuously filled to pressurize to the first heat treatment pressure of 60MPa, and the temperature and pressure are maintained for 90 minutes;

[0035] (2) Continue heating and pressurizing, continue heating to the second heat treatment temperature of 510°C at a heating rate of 3°C / min, and continue to fill with argon gas to pressurize to the second heat treatment pressure of 120MPa, and keep the temperature and pressure at this temperature and pressure for 90min; then cool down to below 200°C, start to release the pressure to room pressure, and set the cooling rate to natural cooling with the furnace to obtain a pre-burned magnetic core;

[0036] (2) Magnetic field heat treatment: The pre-burned magnetic core is placed in the magnetic field heat treatment furnace and heated to 500°C at a heating rate of 10°C / min. At this time, a magnetic field parallel to the width direction of the amorphous strip is added, and the magnetic field intensity is 1500Gs. The magnetic field heat treatment is carried out at this temperature and magnetic field for 90 minutes, and the temperature is cooled to room temperature with the furnace to obtain a magnetic core.

[0037] Examples 2-12 and Comparative Examples 1-4

[0038] The only difference between Examples 2-12 and Comparative Examples 1-4 and Example 1 is: in steps (1)-(3), the heating rate or temperature or pressure of the first heat treatment, the heating rate or temperature or pressure of the second heat treatment, the magnetic field heat treatment temperature or magnetic field intensity and time. The detailed differences are shown in Table 1.

[0039] Example 13

[0040] The difference between the embodiment and embodiment 1 is that in step (1), the alloy is Fe 73.5 Si 15.5 B7Cu1Nb3 amorphous ribbon.

[0041] Table 1

[0042]

[0043]

[0044] The performance of the magnetic core prepared above was tested: the inductance L of the magnetic core was tested using a Keysight Agilent 4294A precision impedance analyzer in an external magnetic field of 1A / m and a frequency range of 1kHz to 100kHz; the effective magnetic permeability μ e Obtained through the inductance L conversion formula:

[0045] μ e =(L×L e ) / (N 2 ×A e ),

[0046] Where, L is the core inductance, μ e is the effective magnetic permeability of the core, L e is the magnetic path length of the core, A eis the effective cross-sectional area of ​​the core, N is the number of coil turns (the test condition is 1 turn), and the test results are shown in Table 2.

[0047] Conventional heat treatment process is the preparation method in Comparative Example 5. Now, the magnetic core prepared in Comparative Example 5 is used as a basis for comparison to calculate the change rate X of the magnetic permeability of the magnetic core of other embodiments of the present invention and the conventional heat treatment process Comparative Example 5: X f =(μ n -μ 对比例5 ) / μ 对比例5 *100%, where μ n Refers to the effective magnetic permeability of a magnetic core obtained in a certain embodiment or comparative example at frequency f, μ 对比例5 Refers to the effective magnetic permeability of the magnetic core prepared in Comparative Example 5 at frequency f. The results are shown in Table 2.

[0048] Table 2

[0049]

[0050]

[0051] It can be seen from Examples 1-12 and Comparative Examples 1-4 that the method of the present invention effectively solves the problems of uneven nucleation and excessive growth of nano-grains in conventional heat treatment, and improves the magnetic permeability in the entire frequency range of 1-100kHz. Specifically in the above embodiments, under the condition of a frequency of 1kHz, the magnetic permeability of the magnetic core is 160,000-250,000, under the condition of 10kHz, the magnetic permeability of the magnetic core is 140,000-200,000, and under the condition of 100kHz, the magnetic permeability of the magnetic core is 35,000-40,000. In addition, it can be observed that, compared with Comparative Example 5, the improvement of the effective magnetic permeability of Examples 1-12 under the conditions of 1kHz, 10kHz and 100kHz is greater than 100%, which confirms that the preparation method of the present invention can achieve the purpose of significantly improving the magnetic permeability in the entire frequency range of 1-100kHz by using the entire amorphous magnetic tape as raw material and undergoing a heat treatment process at a specific temperature and pressure.

[0052] Combination Figure 2 and 4-5 Analysis shows that in conventional heat treatment, samples will have the problem of uneven heating, resulting in uneven nucleation of nano-grains, incomplete precipitation of grains and excessive growth. Therefore, the present invention first performs the first heat treatment to make the amorphous magnetic core evenly heated, providing a basis for the second heat treatment; then the temperature is raised to the second heat treatment temperature, and the pressure is continued to be increased. Through a slow heating rate and the selection of a suitable holding time, it is ensured that the grains have enough time to precipitate at a higher temperature, and grow slowly and evenly under the action of air pressure, avoiding uneven heating caused by overheating, incomplete grain precipitation due to too short a time, or excessive grain growth due to too long a holding time; finally, combined with magnetic field heat treatment, the nano-grains are completely turned, and the force field heat treatment and magnetic field heat treatment as a whole make the grains in the magnetic core precipitate completely and have uniform size, thereby achieving the purpose of improving the magnetic permeability of the magnetic core in the entire frequency band.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a magnetic core, characterized in that: The steps include: (1) subjecting the amorphous magnetic core to a first heat treatment and a second heat treatment in sequence, cooling and reducing the pressure to obtain a pre-burned magnetic core; the temperature of the first heat treatment is 400-480° C., the temperature of the second heat treatment is 490-540° C., the pressure of the first heat treatment is 50-100 MPa, and the pressure of the second heat treatment is 90-160 MPa; (2) The pre-burned magnetic core is subjected to magnetic field heat treatment and cooled to obtain the magnetic core.

2. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the time of the first heat treatment is 70-180 min, and the heating rate of the first heat treatment is 1-30° C. / min.

3. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the time of the second heat treatment is 70-180 min, the heating rate of the second heat treatment is 1-5°C / min, and the cooling rate is 5-200°C / min.

4. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the pressurization methods of the first heat treatment and the second heat treatment are each selected from at least one of pressurization by inert gas pressure and pressurization by mold extrusion; in step (1), the amorphous magnetic core is formed by winding an amorphous strip, and in step (2), the magnetic field direction of the magnetic field heat treatment is parallel to the width direction of the amorphous magnetic core.

5. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%, V 0-10%.

6. The method for preparing a magnetic core according to claim 1, characterized in that: In step (2), the temperature of the magnetic field heat treatment is 460-530° C., the time of the magnetic field heat treatment is 10-180 min, and the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.

7. The method for preparing a magnetic core according to claim 1, characterized in that: In step (1), the cooling and depressurization method is to first naturally cool the system to below 200° C. and then release the pressure of the system to atmospheric pressure; in step (2), the cooling method is natural cooling.

8. A magnetic core made by the method for making a magnetic core according to any one of claims 1 to 7.

9. The magnetic core according to claim 8, characterized in that At a frequency of 1kHz, the magnetic permeability of the magnetic core is 160,000-250,000, at a frequency of 10kHz, the magnetic permeability of the magnetic core is 140,000-200,000, and at a frequency of 100kHz, the magnetic permeability of the magnetic core is 35,000-44,000.

10. Use of the magnetic core according to claim 8 or 9 in the preparation of new energy vehicles, photovoltaic energy storage equipment, electronic camera equipment, and 5G communication equipment.

Citation Information

Cited By

  • Magnetic core having high magnetic permeability, preparation method therefor and use thereof

    WO2026097695A1